Antinomic Understanding of the Secular in Georges Florovsky’s Works - V. A. Shchipkov (Концепт: философия, религия, культура, 2022)
The article analyzes the approach of Georges Florovsky to the problem of the secular (worldly, earthly, immanent). Georges Florovsky gave the secular tendencies in the Christian world a negative assessment as they led to cultural crises. He proposed to seek their origin in the antinomic (God-human, both earthly and heavenly) nature of the Christian church. He deduced that the origins of secular culture stemmed forth from the medieval attempts to break this antinomy, to create Heaven on Earth. This could be seen in the Byzantine Empire (subordination of the Church to the Emperor), in the Latin world (assignment of secular power to the Pope), in the European postReformation thought (through the blurring of the distinction between theology and de-Christianized philosophy), and later in the Russian religious philosophy (attempts to formulate the idea of Christian state). Drawing on the concept of the divine-human antinomy of the Church, Georges Florovsky insisted that the Church should neither try to blur the line between the religious and the secular not try to influence secular politics, but should instead proceed from the fact that culture is intrinsically religious and substantially theologised. In fact, he objected to the ecclesiasticisation of politics and offered to proceed from the assumption that Christianity (religion) is universal by default. Georges Florovsky used a dual, dialectical approach in which secular discourse is seen as a religious one that aspires to secular power and consequently ceases to be religious, creating a kind of secular culture that threatens Christianity itself. In order to overcome this secular culture Christianity is called upon to abstain from direct political influence on it. While avoiding limitations of the religious-secular dualism of the Enlightenment and allowing the Church thought to prevent aggravating relations with secular politics, this approach fails to properly distinguish between the causes and the effects of the secular discourse. The conclusion identifies ways of furthering Florovsky’s approach and thought.